المميزات الأنثروبولوجية و المجتمع الأثني في الحبشة في العصر الوسيط - بن خيرة, أحمد; غانية, البشير; بن عمر, علال (جامعة الوادي - University of Eloued, 2021)
لا شك أن موضوع المكون البشري لأي مجتمع وخصائصه الأنثروبولوجية تعتبر من المواضيع الشائكة ، وبالرغم من ذلك فقد حاولنا طرق هذا الموضوع من بوابة الحبشة اذا تناولنا المجال الجغرافي والمكون البشري ثم الإنسان المهاجر الذي وطأ هذه البلاد ،وما توالت عليها من هجرات للحاميين و الساميين عبر مختلف الفترات التاريخية ،وما رافقتها عملية الامتزاج البشري التي حدثت في هذا الركن الجغرافي مما خلق نوع من التشكيلة الاجتماعية التي ميزت مجتمع الحبشة عن غيره. There is no doubt that the issue of the human component of any society and the anthropological characteristics of the thorny topics, and despite this we tried to approach this topic from the gate of Abyssinia if we dealt with the geographical area and the human component, then the human migrant who set foot in these countries, and the subsequent migrations of the Hamites and Semites through various historical periods And what was accompanied by the process of human mixing that occurred in this geographical corner, which created a kind of social formation that distinguished Abyssinian society from others.
مقال
Keywords: الحبشة ؛ الزيلع ؛ الحاميون ؛ الساميون ؛ اليمن; Abyssinia; Al Zaila; Hamites; Semites; Yemen